Percutaneous Coronary Intervention With and Without Intravascular Ultrasound for Patients With Complex Lesions: Utilization, Mortality, and Target Vessel Revascularization. (11th May 2022) - Hannan, Edward L.; Zhong, Ye; Reddy, Pavan; Jacobs, Alice K.; Ling, Frederick S.K.; King III, Spencer B.; Berger, Peter B.; Venditti, Ferdinand J.; Walford, Gary; Tamis-Holland, Jacqueline
Abstract : Background: Intravascular ultrasound (IVUS) has several benefits during percutaneous coronary interventions (PCIs), including more accurate vessel sizing, improved stent expansion, and better strut apposition. Prior clinical trials have demonstrated a reduction in cardiac events when IVUS is used. However, there is limited information about the utilization of IVUS and the outcomes of IVUS-guided versus angiography-guided PCI in patients with complex lesions in a contemporary population-based setting. Methods: New York's PCI registry was used to identify 44 305 patients with complex lesions (lesions that complicate stenting or that require multiple stents) undergoing PCI with and without IVUS guidance and discharged between December 1, 2013 and November 30, 2018. Trends and inter-hospital variation in IVUS use were examined. Risk-adjusted mortality and target vessel revascularization were compared. Results: A total of 6174 (13.9%) PCI patients underwent IVUS-guided PCI. The median follow-up period was 2.5 years. The percent of patients with complex lesions who underwent IVUS-guided PCI rose from 13.4% in 2014 to 16.5% in 2018 ( P <0.0001 for trend), with the main increases occurring in the last 2 years of the period. Only 31 of 66 hospitals in the study used IVUS for >5% of their study patients. IVUS-guided PCI patients experienced significantly lower mortality (adjusted hazard ratio=0.89 [0.79–0.98] after adjustment using a Cox proportional hazards model, and HR=0.88 [0.78–0.99] for propensity-matched patients). We also found that IVUS-guided PCI patients had a lower rate of target vessel revascularization (adjusted hazard ratio=0.88 [0.80–0.97]) after adjusting using Cox proportional hazards with competing risk of mortality and after propensity matching (0.88 [0.79–0.99]). Conclusions: Utilization of IVUS for complex lesions has increased but contemporary rates remain low, and there are large inter-hospital variations. The use of IVUS for complex lesions was associated with lower risk of medium-term mortality and target vessel revascularization.